Bemisia afer sensu lato, a Vector of Sweet potato chlorotic stunt virus - Gamarra, HA; Fuentes, S.; Morales Garzón, Francisco José; Glover, R.; Malumphy, C; Barker, Ian (Scientific Societies, 2010)
Bemisia tabaci biotype B is considered to be the primary vector of Sweet potato chlorotic stunt virus (SPCSV, Crinivirus). However, Trialeurodes abutiloneus also has been shown to transmit SPCSV in a semipersistent manner. Mixed infection of SPCSV with the aphid-transmitted Sweet potato feathery mottle virus (SPFMV, Potyvirus) causes sweetpotato (Ipomoea batatas) virus disease (SPVD), the major virus disease affecting this crop. High populations of B. afer sensu lato are seasonally associated with sweetpotato in Peru during times of low B. tabaci incidence. The transmission of SPCSV (in single and double infection with SPFMV) by laboratory-reared B. afer sensu lato and B. tabaci biotype B was investigated. For SPCSV transmission efficiency, individual adult insects were allowed 48 h for acquisition and inoculation access periods at both 20 and 25°C. SPCSV was transmitted by both whiteflies, with similar transmission efficiency when the virus was acquired from plants singly infected by SPCSV or doubly infected with SPCSV and SPFMV, at 20 and 25°C. We conclude that B. afer sensu lato is a newly identified vector of SPCSV. This finding may have important epidemiological significance for the spread of SPCSV and SPVD.